Affect, Alpha Function, and the Very Small: A Reconsideration of Teacher Workload - Downey, Adrian (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2023)
In this paper, I draw together myriad theoretical and philosophical sources to think through the intensification of emotion amid and emerging from the COVID-19 pandemic. I begin with three narratives from my own teaching and learning, which ground the subsequent conversation. I then characterize the current movement in educational theorizing known as the affective turn. The affective turn, I suggest, attunes educational inquiry to small, yet vital, moments of classroom interaction often taken for granted in public education. Toward considering those vital moments in more nuance, I discuss psychoanalyst Wilfred R. Bion’s notion of the alpha function – a nonconscious digestion of emotion we perform for others when they are overwhelmed. When coupled with Nel Noddings’ evocation of the ethics of care in education, the alpha function offers an understanding of the hidden emotional labour in teaching. This hidden dimension of the teacher’s task, the portion of the job that deals in regulating our own emotions and in helping students make sense of theirs, I suggest, is becoming more difficult amid the affective situation of the COVID-19 pandemic. I conclude the paper by gesturing toward a threefold response to be taken up more fully elsewhere: humility before the task of teaching, a reverence for the work of feeling, and a willingness to organize toward a more caring school system.